Markers of gastrointestinal permeability and dysbiosis in premenopausal women with PCOS : a case-control study - Lingaiah, Shilpa; Arffman, Riikka K.; Morin-Papunen, Laure; Tapanainen, Juha S.; Piltonen, Terhi (BMJ Open, 2021)
Objectives Altered intestinal permeability and gut barrier dysfunction have been suggested to play a role in the pathogenetic mechanism of polycystic ovary syndrome (PCOS), the most common endocrine and metabolic condition in reproductive-aged women. However, data on intestinal permeability and dysbiosis of the gut microbiota in PCOS is still limited, with conflicting results. To this end, the concentrations of gastrointestinal permeability and gut dysbiosis markers were analysed in women with PCOS. Design Case-control study. Setting General community. Participants 104 women with PCOS and 203 body mass index (BMI) matched control women at age 46. Primary and secondary outcome measures Serum levels of zonulin, fatty acid-binding protein 2 (FABP2), urinary levels of indican, and hormonal and metabolic parameters. Results Serum levels of zonulin (128.0 +/- 17.0 vs 130.9 +/- 14.0 ng/mL, p=0.13) and FABP2 (1.5 +/- 0.9 vs 1.5 +/- 0.7 ng/mL, p=0.63) and urinary levels of indican (9.5 +/- 5.5 vs 8.4 +/- 4.2 mg/dL, p=0.07) were comparable in women with PCOS and controls in the whole study population. Likewise, when the study population was divided into different BMI groups as normal weight, overweight and obese, the levels of the above markers were comparable between the study groups. After BMI adjustment, zonulin levels correlated with the levels of high-sensitivity C reactive protein and homoeostasis model assessment of insulin resistance (p Peer reviewed